Respuesta :

The answer is 1 because you have to Substitute Two form X then it would just be Then substitute 2 form 1 and you would get 1
Ver imagen taytay1029
MsRay

Answer:

(-1, -1)

Step-by-step explanation:

Given the two equations:

y = x and y = 2x +1, since both expressions are equal to 'y', you can set them equal to each other and first solve for x:

x = 2x + 1

Subtract '2x' from both sides: x - 2x = 1 or -x = 1

Divide both sides by '-1': -x/-1 = 1/-1 or x = -1

Since y = x, then y = -1

Solution point is (x, y) or (-1, -1)